Multiple Religious Belonging among visitors of Dominican spiritual centers in the Netherlands. Issue 3 (2nd September 2018) - Liefbroer, Anke I.; van der Braak, André F. M.; Kalsky, Manuela
ABSTRACT: In the religiously pluralized Western world, a trend called 'Multiple Religious Belonging' (MRB) has been identified. Although it is a much theologically debated concept, empirical research on the practice of MRB is limited. The present research project therefore explores the phenomenon of MRB among visitors of Dominican spiritual centers in the Netherlands (n=472). It investigates to what extent and in which ways such visitors combine elements from more than one religious tradition in their lives and what they perceive to be the benefits of combining elements. It links this information to their views on religion, the resources they draw from, their (religiously diverse) networks, and their motivations for attending spiritual activities. The results indicate that respondents who combine elements from more than one religious tradition ('combiners') are more likely than 'non-combiners' to: a) see religion as something that is constantly changing during the life course; b) have networks which are religiously diverse; c) place importance on nature, in-depth conversations, personal rituals or practices, and theological, philosophical, and spiritual texts as resources; d) be motivated to attend spiritual centers because of a focus on self-exploration.